2022
DOI: 10.3390/cancers14020404
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Extracellular Matrix and Tumor-Infiltrating Immune Cells in the Prognostication of High-Grade Serous Ovarian Cancer

Abstract: Ovarian cancer is the eighth global leading cause of cancer-related death among women. The most common form is the high-grade serous ovarian carcinoma (HGSOC). No further improvements in the 5-year overall survival have been seen over the last 40 years since the adoption of platinum- and taxane-based chemotherapy. Hence, a better understanding of the mechanisms governing this aggressive phenotype would help identify better therapeutic strategies. Recent research linked onset, progression, and response to treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 78 publications
1
8
0
Order By: Relevance
“…In addition, more meta-analyses have shown that potentially functional polymorphisms of IL12A and IL12B are thought to increase the risk of malignancies such as gastric, lung, and cervical cancers ( 43 45 ). TLL1 is significantly upregulated in OC patients and has been suggested as a prognostic marker in OC patients ( 46 , 47 ), and the same results were obtained in our study. Zou et al.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, more meta-analyses have shown that potentially functional polymorphisms of IL12A and IL12B are thought to increase the risk of malignancies such as gastric, lung, and cervical cancers ( 43 45 ). TLL1 is significantly upregulated in OC patients and has been suggested as a prognostic marker in OC patients ( 46 , 47 ), and the same results were obtained in our study. Zou et al.…”
Section: Discussionsupporting
confidence: 92%
“…Other genes, while not yet described in cervical cancer, have been found to be prognostic in ovarian cancer ( RGS11 [ 31 ], CHAD and CBLN2 [ 32 ], NETO1 [ 33 ], HSPE1 [ 34 ], and BIRC6 , which Lnc-TTC27–9 is intronic to [ 35 ]). The expression of SH3BP5 is reduced in ovarian cancer samples compared to normal tissue and that silencing of Sab protein expression may lead to chemo-resistance [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other genes, while not yet described in cervical cancer, have been found to be prognostic in ovarian cancer (RGS11 [30], CHAD and CBLN2 [31], NETO1 [32], HSPE1 [33], and BIRC6 which Lnc-TTC27-9 is intronic to [34]). Expression of SH3BP5 is reduced in ovarian cancer samples compared to normal tissue and that silencing of Sab protein expression may lead to chemo-resistance [35].…”
Section: Resultsmentioning
confidence: 99%